PREVALENCE OF ANXIETY DISORDER AMONG HEALTHCARE WORKERS AT SAINT PAUL HOSPITAL DURING THE COVID-19 PANDEMIC: EXPLORING ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the current situation and analyze some factors related to anxiety disorder amonghealthcare workers during the COVID-19 pandemic and some related factors.Subjects and Methods: We conducted a cross-sectional descriptive study involving 922 Saint PaulHospital staff members who willingly participated in the research. Anxiety disorder levels wereassessed using the GAD-7 scale. We examined relevant factors such as demographic characteristicsand the work environment of healthcare workers during the pandemic.Results: The study found that the prevalence of anxiety disorder among medical staff at Saint PaulGeneral Hospital was 38.8%. Several factors were identified as significantly associated with higherrates of anxiety disorder, including being male, single, having less than 10 years of service, workingmore than 5 days per week, and working more than 8 hours per day.Conclusion: The research revealed a relatively high prevalence of anxiety disorder (38.8%) amonghealthcare workers at Saint Paul Hospital during the COVID-19 pandemic. Additionally, the studyhighlighted that longer working hours, gender, and singer status were significant contributing factorsto the increased occurrence of anxiety disorder among healthcare workers.
Keywords: Anxiety disorder, healthcare workers, COVID-19, GAD-7.